Texturally Controlled U–Th–Pb Monazite Geochronology Reveals Paleoproterozoic UHT Metamorphic Evolution in the Khondalite Belt, North China Craton. (19th February 2020) - Jiao, Shujuan; Fitzsimons, Ian C W; Zi, Jian-Wei; Evans, Noreen J; Mcdonald, Brad J; Guo, Jinghui
Abstract: Sapphirine-bearing UHT granulites from the Dongpo locality in the Khondalite Belt of the North China Craton have been comprehensively characterized in terms of petrology, mineral chemistry, metamorphic evolution and zircon geochronology. However, the precise timing of the peak-UHT metamorphism and other key stages in the P – T – t evolution remain controversial due to the complexity of multiple metamorphic overprints and the lack of petrographic context for zircon age data. In this study, monazite from four samples of the Dongpo granulite are divided into six groups based on chemical composition and textural context, and dated ( in-situ SHRIMP and LA–ICP–MS U–Pb). An age population of 1·91–1·88 Ga was obtained from high-Y cores of monazite inclusions in garnet (Group 1) and on grains in the rock matrix (Group 2). The maximum age of c .1·91 Ga is interpreted as the minimum timing for prograde metamorphism before UHT metamorphism (M1). An age population of 1·90–1·85 Ga was obtained from low-Y domains of monazite inclusions (Group 3) and of matrix grains (Group 4). Combined with previous zircon dating results, the age population from low-Y Mnz constrains the timing and duration of the UHT metamorphism to 1·90–1·85 Ga and 50 (±15) million years, respectively. The large (50 m.y.) age spread is interpreted to reflect continuous monazite formation, and it is consistent with the slow post-peak near-isobaric cooling stage (M2). An age of c .1·86 Ga was obtained from monazite in textural contact with sapphirine/spinel + plagioclase intergrowths (Group 5), which is interpreted as the timing of the subsequent decompression–heating stage (M3). The younger age clusters at c .1·80 and 1·77 Ga, obtained from Th-rich monazite rims (Group 6) and one single Th-depleted monazite in textural contact with matrix biotite, respectively, indicate dissolution–reprecipitation and new monazite growth from fluid released by crystallizing anatectic melt during retrogression. These results, along with the previous 1·93–1·91 Ga data for UHT metamorphism, suggest that there was a very long-lived Paleoproterozoic UHT metamorphism (1·93–1·85 Ga) in the Khondalite Belt of the North China Craton. This supports the large hot orogeny model for the generation of Paleoproterozoic UHT metamorphism in the Khondalite Belt during the amalgamation of the Nuna supercontinent.